SOCIO-ECONOMIC DETERMINANTS OF MALE STUDENTS’ RETENTION IN PUBLIC SECONDARY SCHOOLS IN MBOONI WEST SUB-COUNTY, MAKUENI COUNTY, KENYA - RUTH NTHAMBA MAUNDU (Machakos University Press, 2025)
There have been several awareness campaigns of girls’ retention in school, which have started bearing fruit. However, the welfare of the male student has largely been overlooked. Despite the Kenya government providing Free Day Secondary Education (FDSE), the issue of the male student has not been sufficiently addressed. This study sought to investigate the Socio-economic determinants of the male students’ retention in public secondary schools in Mbooni West Sub-County, Makueni County, Kenya. The objectives of the study were be to establish how the cultural practices, peer pressure, parents’ level of education and parental income affect male students’ retention in public secondary schools in Mbooni West Sub-County. The research was guided by theory of Maslow's Hierarchy of Needs (1943). A descriptive survey design was adopted. The target population comprised 38 principals, 76 class teachers, 1,140 male students (in forms two and three) and 114 parents. The researcher used multistage sampling. Random sampling was used to select 15 school out of 38 and 15 principals were selected using purposive sampling. Simple random sampling was used to select 30 class teachers of form two and three. From 1,140 male students, 456 were selected using proportionate random sampling. From the 114 parents three from each of the 15 sampled schools were selected using random sampling, giving a total of 45 parents. The overall sample size was 546 respondents. Data collection instrument included questionnaires for class teachers and male students and interviews schedules for principals and parents. A pilot study was conducted in Mbooni East Sub-County to ascertain the validity and reliability of the instruments using 10% of the target population. Quantitative data was analyzed using descriptive statistics (means, frequencies percentages, tables, pie charts and bar graphs) and inferential statistics (Pearson Moment Relationship) to determine the significance and relationship between the variables. Qualitative data was analyzed thematically along the specific objectives and presented in narrative form. Data analysis was conducted using the Statistical Package for Social Sciences (SPSS) version 27. The study findings showed a moderate negative correlation between cultural practices and the male student retention at school (p= 0.000; r= -0.043) basing on students’ respondents, there was a weak negative association between the peer pressure and male retention (p = 0.000; r = -0.217), there was no significant association between the parental level of education and male retention because the p- values were greater than the alpha values in all other respondents except, the parents who showed that there was a significant association ((p = 0.060; r = -0.279) and correlation between the parental income and male retention was not significant except in the parents, were there was negative moderate correlation ( (p = 0.000; r = -0.388). The study therefore concluded that socio-economic determinants were found to have a significant influence on male retention. From the findings the researcher recommends that the school should establish male student welfare programs to address gender-specific challenges and introduce motivational initiatives tailored to male students’ needs, the school should engage guest speakers to mentor and guide students on how to positively navigate peer influence, parents should be educated on the critical role they play in their children’s education through mandatory school-based sensitization meetings. Parents should be encouraged to develop new income-generating strategies to enhance their ability to pay school fees and meet their sons' educational needs.